Effects of household solid fuel use on sarcopenia in middle-aged and older adults: evidence from a nationwide cohort study - Su, Shaohui; Zhou, Yinuo; Wang, Kerui; Liu, Aonan; Lei, Lei; Ma, Hao; Yang, Yanfang (Frontiers in Public Health, 2024)
Background: Household solid fuel use is common in global households and has been linked to changes in handgrip strength and muscle mass. However, whether household solid fuel use results in sarcopenia over time is not well elaborated.: This study employed data from the 2011-2015 China Health and Retirement Longitudinal Study (CHARLS) that recruited 4932 participants ≥45 years. The Cox proportional hazards regression model was conducted to estimate the impact of household solid fuel use for cooking and heating on sarcopenia development. The analysis was further stratified based on geographic position. Mediation analysis was employed to estimate the potential mediating effects of cognitive function and depressive symptoms associated with household solid fuel use and sarcopenia.Results: Over the four-year follow-up, 476 cases of sarcopenia were reported (9.65%), with 254 in males (10.82%) and 222 in females (8.59%). Cooking and heating with solid fuels increased the risk